Efecto de la mancha negra (Phytophthora spp.) en el cultivo de Cacao (Theobroma cacao L.) en el Ecuador - Franco Apupalo, Pedro Ramon (2023)
Cocoa (Theobroma cacao L.) is an important crop in the world, especially in tropical countries. But throughout history, the cocoa industry has been devastated due to rampant decline caused by emerging diseases caused by various pathogens, including Phytophthora spp. The objective was to detail information about black spot (Phytophthora spp) in cocoa cultivation. The methodology used consisted of collecting information from updated texts, magazines, virtual libraries and academic articles that contributed to the development of this instrument. The results detail that cocoa is of importance worldwide and its yield is low, due to the incidence of Phytophthora spp. The conclusions determine that Phytophthora spp attacks roots, leaves, stems and branches of cocoa, from nursery stages to adult plants, but the most serious damage occurs in the pods, which can be attacked at any stage of development, producing a dark brown spot. with slightly irregular margins; The greatest damage caused is infections in the fruits. One of the first symptoms observed is the appearance of small darkened spots on the surface of the peel visible approximately 30 hours after infection in fruits at any stage of development. As methods of cultural control, shading through pruning, weed control, techniques for evacuating excess water and weekly removal of diseased fruits are mentioned; chemical control uses synthetic fungicides composed of copper, metalaxyl and phosphonates and biological control, Trichoderma, Penicillium, Gliocladium, Rhodotorula, Candida Pseudomonas and Bacillus.